2016
DOI: 10.1631/jzus.b1600014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taurine and housing density on renal function in laying hens

Abstract: This study investigated the putative protective effects of supplemental 2-aminoethane sulfonic acid (taurine) and reduced housing density on renal function in laying hens. We randomly assigned fifteen thousand green-shell laying hens into three groups: a free range group, a low-density caged group, and a high-density caged group. Each group was further divided equally into a control group (C) and a taurine treatment group (T). After 15 d, we analyzed histological changes in kidney cells, inflammatory mediator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Generally, birds placed on 0.004 to 0.008% dietary taurine-supplemented diets possess higher and varied amounts of the studied antioxidant biomolecules both in the liver and in the kidney. The report of this research correlates with the finding of Ma et al (2016) that reported an increase in the activity of total antioxidant capability of laying hens when their diets were supplemented with taurine. Anand et al, 2010 also reported a significant (p<0.05) increase in the liver GSH level of the orally taurine administered rats at a dose of between 50 mg to 500 mg in 50% normal saline, but a reduction in the rats' kidney GSH level as compared with the control group.…”
Section: Discussionsupporting
confidence: 88%
“…Generally, birds placed on 0.004 to 0.008% dietary taurine-supplemented diets possess higher and varied amounts of the studied antioxidant biomolecules both in the liver and in the kidney. The report of this research correlates with the finding of Ma et al (2016) that reported an increase in the activity of total antioxidant capability of laying hens when their diets were supplemented with taurine. Anand et al, 2010 also reported a significant (p<0.05) increase in the liver GSH level of the orally taurine administered rats at a dose of between 50 mg to 500 mg in 50% normal saline, but a reduction in the rats' kidney GSH level as compared with the control group.…”
Section: Discussionsupporting
confidence: 88%
“…Dietary taurine (0.1%) was shown to significantly alleviate NF-κB DNA-binding activity in chicken liver [ 363 ] and layer oviduct tissue [ 364 ], which was initially increased due to high-density housing systems. Interestingly, in the chicken renal tissue, the same dose of dietary taurine was able to decrease the NF-κB DNA-binding activity only in the low-density housing environment [ 365 ].…”
Section: Nutritional Modulation Of Nf-κb In Poultrymentioning
confidence: 99%
“…Even though it has been shown that diets supplemented with taurine can improve the taurine deposition in egg yolks [8] and can have benefits for kidneys [9], the cost of dietary taurine supplementation is significant. So, other methods have been used to improve taurine deposition in animal production.…”
Section: Introductionmentioning
confidence: 99%